SPENT BULLET INJURIES IN THE HEAD AND NECK REGION - Akhtar, M.; Nabi, G.; Ghani, R.; Mohammad, Gul (Journal of Ayub Medical College Abbottabad, 1992)
ABSTRACT: There is increasing incidence of various injuries caused by wandering spent bullets. These injuries have been encountered in Head and Neck regions, upper limbs and trunk. They can cause severe morbidity and can prove to be fatal. Many such cases have not been reported in literature. There are two reports available in literature, one from Jordan by Hanieh and other from Peshawar (Pakistan) by Rafiq Khan et al. We report another case of the same nature.